Criticality search of soluble boron iteration in MC code JMCT. (September 2017) - Rui, Li; LingYu, Zhang; DunFu, Shi; Li, Deng
Abstract: The soluble boron is used to control the reactivity in normal operation and accident of pressurized water reactor. A criticality search of soluble boron iteration algorithm based on neutron balance is implemented in the Monte Carlo neutron-photon transport code JMCT. Firstly, the interpolation methods and our algorithm of soluble boron iteration are well introduced and compared. Then, the boron concentration of BEAVRS in hot zero power is calculated and compared to the measured data to validate the algorithm.